Preserved Self-Evaluation in Amnesia Supports Access to the Self through Introspective Computation - Juskenaite, Aurelija; Quinette, Peggy; Laisney, Mickaël; Eustache, Marie-Loup; Desgranges, Béatrice; Viader, Fausto; Eustache, Francis (Frontiers in Human Neuroscience, 2016)
Encounters with new people result in the extraction and storage in memory of both their external features, allowing us to recognize them later, and their internal traits, allowing us to better control our current interactions with them and anticipate our future ones. Just as we extract, encode, store, retrieve and update representations of others so, too, do we process representations of ourselves. These representations, which rely on declarative memory, may be altered or cease to be accessible in amnesia. Nonetheless, studies of amnesic patients have yielded the surprising observation that memory impairments alone do not prevent patients from making accurate trait self-judgments. In this review, we discuss prevailing explanations for preserved self-evaluation in amnesia and propose an alternative one, based on the concept of introspective computation. We also consider molecular and anatomical aspects of brain functioning that potentially support introspective computation.